The Understanding of Scalar Implicatures in Children With Autism Spectrum Disorder: Dichotomized Responses to Violations of Informativeness - Schaeken, Walter; Van Haeren, Marie; Bambini, Valentina (Frontiers in Psychology, 2018)
This study investigated the understanding of underinformative sentences like “Some elephants have trunks” by children with autism spectrum disorder (ASD). The scalar term ‘some’ can be interpreted pragmatically, ‘Not all elephants have trunks,’ or logically, ‘Some and possibly all elephants have trunks.’ Literature indicates that adults with ASD show no real difficulty in interpreting scalar implicatures, i.e., they often interpret them pragmatically, as controls do. This contrasts with the traditional claim of difficulties of people with ASD in other pragmatic domains, and is more in line with the idea that pragmatic problems are not universal. The aim of this study was to: (a) gain insight in the ability of children with ASD to derive scalar implicatures, and (b) do this by assessing not only sensitivity to underinformativeness, but also different degrees of tolerance to violations of informativeness. We employed a classic statement-evaluation task, presenting optimal, logical false, and underinformative utterances. In Experiment 1, children had to express their judgment on a binary option ‘I agree’ vs. ‘I disagree.’ In Experiment 2, a ternary middle answer option ‘I agree a bit’ was also available. Sixty-six Flemish-speaking 10-year-old children were tested: 22 children with ASD, an IQ-matched group, and an age-matched group. In the binary judgment task, the ASD group gave more pragmatic answers than the other groups, which was significant in the mixed effects logistic regression analysis, although not in the non-parametric analysis. In the ternary judgment task, the children with ASD showed a dichotomized attitude toward the speaker’s meaning, by tending to either fully agree or fully disagree with underinformative statements, in contrast with TD children, who preferred the middle option. Remarkably, the IQ-matched group exhibited the same pattern of results as the ASD group. Thanks to a fine-grained measure such as the ternary judgment task, this study highlighted a neglected aspect of the pragmatic profile of ASD, whose struggle with social communication seems to affect also the domain of informativeness. We discuss the implications of the dichotomized reaction toward violations of informativeness in terms of the potential role of ASD and of cognitive and verbal abilities.